Gambaran Administrasi Rekam Medis Semi-Digital berdasarkan Pendekatan 5M dan POAC di RSU X Kota Depok Tahun 2025 - Shinta, Dewi; Hartono, Risky Kusuma; Rum, Malihah Ramadhani (Jurnal ARSI : Administrasi Rumah Sakit Indonesia, 2026)
Medical record administration is an essential component in supporting healthcare service quality. During the transition toward Electronic Medical Records (EMR), many hospitals still use semi-digital systems that combine conventional and electronic processes. This study aimed to describe semi-digital medical record administration at RSU X, Depok City, based on the Man, Money, Material, Method, and Machine (5M) management elements and the Planning, Organizing, Actuating, and Controlling (POAC) management functions. This study employed a descriptive qualitative approach through in-depth interviews and observations involving five informants. The results showed that the semi-digital system operated through the parallel use of physical medical records and the EMR system. In terms of Man, only four staff members had a medical record educational background, and training had not been equally provided. Regarding Money, budgeting was managed by the central management. For Material, storage facilities did not meet standards, particularly storage racks, tracers, and color-coding systems. In terms of Machine, technical problems with computers and printers were still encountered. Regarding Method, implementation complied with the Indonesian Ministry of Health Regulation No. 24 of 2022 through 15 Standard Operating Procedures covering manual and digital processes. The implementation of POAC functions was not optimal because coordination and supervision remained limited to the unit coordinator level without active involvement from the department head. This study indicates that the semi-digital system at RSU X Depok City has not been fully integrated and requires improvements in human resources, infrastructure, and policy support to ensure an effective transition toward full EMR implementation.